Analisis Yuridis Terhadap Tindak Pidana Permufakatan Jahat Menjadi Perantara Narkotika Dalam Putusan Nomor 295/Pid.Sus/2025/Pt Pdg - Doni Eka Putra (Journal of Global Legal Review, 2025)
Drug-related offenses are classified as extraordinary crimes due to their widespread and systemic impact on public health, national security, and future generations. One of the legal mechanisms used to prosecute drug offenders is Article 114 paragraph (1) in conjunction with Article 132 paragraph (1) of Law No. 35 of 2009 on Narcotics, which criminalizes conspiracy to become an intermediary in the sale and purchase of narcotics. This article analyzes the decision of the Padang High Court in case No. 295/PID.SUS/2025/PT.PDG, which affirmed the district court’s finding of guilt against the defendant, Yusri Gusmadi, but significantly reduced the prison sentence from seven years to two years. Using a normative legal method and case-based approach, this study evaluates whether the elements of criminal conspiracy as an intermediary were proven beyond a reasonable doubt. The analysis also critically reviews the reasoning provided by judges in both the first and appellate court decisions. The findings show that the court's conviction was not fully supported by clear and convincing evidence regarding the defendant's active involvement in the drug transaction. Moreover, the reduction of the sentence in appellate court contradicts the mandatory minimum punishment stipulated by the Narcotics Law. This paper recommends a more proportionate legal treatment based on the defendant’s actual role and intention, along with greater judicial consistency in narcotics cases.